Pelatihan Pemamfaatan Pestisida alami Berbahan lokal untuk Pencegahan Vektor Demam Berdarah Dengue (DBD) di Kelurahan Kelapa Lima Kota Kupang - Almet, Julianty; Wuri, Diana A; Laut, Meity M; Detha, Annytha I R (International Journal of Community Service Learning, 2021)
Community Service Activities have been carried out in Kelapa Lima Village. This activity aims to provide information and knowledge to the public about the dangers of dengue hemorrhagic fever and its preventive measures through the use of potential mosquito repellent plants. Mosquito repellent plants can be found in the yard of the house so that the community can provide land in the yard of their house to plant these plants that have the potential to act as mosquito repellent. The method used in this service activity is in the form of counseling, training, and cultivating plants as an anti-mosquito agent that causes dengue hemorrhagic fever. The conclusion obtained is an increase in the knowledge of the public's understanding of Dengue Hemorrhagic Fever, an increase in public understanding of the bio-ecology of the vector that causes dengue hemorrhagic fever, utilizing plants that have the potential to act as mosquito repellents.